Experimental investigation of the performance of an air type photovoltaic thermal collector system with fixed cooling fins - Zhonghua Zhao; Li Zhu; Yiping Wang; Qunwu Huang; Yong Sun (Energy Reports, 2023)
Solar energy may now be captured in two ways: heat extraction in solar collectors and electricity generation in photovoltaic panels. It may effectively reduce the degradation of PV cell efficiency caused by overheating of the battery by collecting the heat from the PV/T system. The heat dissipation cooling fin is directly mounted to the rear of the solar panel in this study and coated with an insulating layer to create an air-cooling channel. The heat dissipation fin transfers heat from the back of the photovoltaic panel to a certain mass flow of air in the flow channel, resulting in combined heat and power. The electrical and thermal capabilities of three distinct fin numbers were studied by monitoring electrical power and temperature data. A fixed mass flow rate (0.011 kg/s) for air, three different numbers of fins (0-5-10) and solar irradiance (200 W/m2–600 W/m2) are the experimental conditions. After the system was run stably for 10 min, the average temperature of the back of the PV panel, the device’s inlet and outlet temperatures, and the PV panel’s electric power were recorded. These figures are used to calculate the PV/T system’s electrical and thermal efficiency. When the median electrical efficiency of the three types of fins is compared with varying solar irradiation, it is discovered that the electric efficiency value of the three types of fins is approximately 16%, with a difference of less than 0.6%. The comprehensive efficiency of five groups of fins and ten groups of fins was 61.08% and 69.85%, respectively, based on the median comparison of photoelectric photothermal comprehensive efficiency. The overall efficiency of the zero groups of fins was 26.27%, which was only 14.59% greater than the control plate, and there was a considerable difference between the five and ten groups of fins. This suggests that selecting the right number of fins has a substantial impact on improving PV/T thermal performance. This research will assist in further optimizing the design of PV/T systems for heat collection and will provide valuable information for PV/T system application in building integration.